Transport critical current density of Ag-sheathed (Tl,Cr)Sr2CaCu2O7 high temperature superconductor tapes - A-Hamid N.; Abd-Shukor R. (2023)
Ag-sheathed Tl-1212 tapes with a nominal composition of (Tl1.2Cr0.15)Sr2CaCu2O7 were fabricated using the powder-in-tube (PIT) method. The tapes (approximately 3-4 cm long) were annealed in oxygen flow at 820 C, 870 C and 890 C each for 30 minutes, 1 hour and 5 hours, respectively. The x-ray diffraction (XRD) patterns for samples annealed at 820 C and 870 C showed the Tl-1212 as the dominant phase with Tl-1201 as minor phase. Scanning electron micrographs (SEM) revealed that the tapes showed no discernible favourable texture. Using a self-field approximation together with Jc dependence on temperature the characteristic length (Lc) associated with the pinning force is estimated to be approximately the same as the average grains size (Rg) for the tapes annealed at 820 C for 30 minutes. For tapes that were annealed at 870 C and 890 C, Lc>Rg. The initial rapid suppression of Jc at low fields (<0.1 T) can be attributed to the weak-links phenomena as observed in other polycrystalline high-Tc materials with random grain orientations.